Kalinaw a rain-harvest centered water management model integrated into a wellness resort - Yao, Danica Jeanelle (College of Architecture, University of the Philippines Diliman, 2019)
Through the development of a water management model incorporated into a wellness resort, this thesis aims to raise community awareness on the importance of water usage and user responsibility as a prime example of a self-supportive recreational facility in terms of water management. The model uses a five-step model derived from a harvest-store-use strategy in which water is collected from catchment systems, treated through various filtration systems and ultraviolet light, then used for multiple cycles onsite. The use of an integrative approach - developing a rainwater harvest system simultaneously with the design development of a wellness resort - is highlighted for the added possibilities of streamlining design components and leaving room for future growth. The project tackles both the inaccessibility and the growing challenges of sourcing portable water, a common issue across the country particularly along its highway systems and urban centers, and the lack of awareness surrounding it. The resulting model may be used in the future for similar building applications to augment the available water supply.